Free-living amoebae and their role in Piscirickettsia salmonis transmission in Chilean Salmon aquaculture: insights from in vitro and in vivo studies - Gómez, Fernando A.; Milesi, Bruno; Marshall, Sergio H. (Frontiers in Microbiology, 2026)
Piscirickettsia salmonis is the causative agent of Rickettsial Septicemia (SRS), a severe disease threatening the sustainability of the growing salmon farming industry in Chile. This pathogen significantly impacts fish throughout their life cycle in the ocean, affecting pathogen-free individuals sourced from certified hatcheries. Systematic outbreaks often lead to catastrophic losses near harvest time, suggesting that primary infections originate from an environmental source that remains largely unidentified. Given the ubiquitous nature of free-living amoebae (FLA), we investigated their potential role as reservoirs and vectors for P. salmonis. We focused on Acanthamoeba castellanii and Vannella sp., two FLA species associated with salmon populations. Using immunofluorescence and quantitative PCR (qPCR), we demonstrated that P. salmonis can be internalized, replicate, and be released by both amoeba species. Furthermore, P. salmonis showed an upregulation on its Dot/Icm secretion system, essential for intracellular replication, during this process. While Vannella sp. exhibited pathogen-induced lysis after 72 h, A. castellanii maintained the bacteria more stably. Our findings indicate that A. castellanii acts as a reservoir and vector for P. salmonis, potentially contributing to the persistence and spread of this pathogen in aquatic environments. This enhanced understanding of the pathogen’s life cycle has implications for developing improved disease control strategies.